Artifact quantification of venous stents in the MRI environment: Differences between braided and laser-cut designs. (August 2021) - Reiss, Simon; Özen, Ali Caglar; Lottner, Thomas; Dlaikan-Campos, Nasib; Düring, Klaus; Massmann, Alexander; Bock, Michael
Highlights: MRI in novel venous stents is not impaired by susceptibility-induced artifacts. RF-induces artifacts are more complex in braided compared to laser-cut stents. Braided stents can enhance the intraluminal signal due to B 1 amplification. Abstract: Purpose: To quantify B 0 - and B1 -induced imaging artifacts of braided venous stents and to compare the artifacts to a set of laser-cut stents used in venous interventions. Methods: Three prototypes of braided venous stents with different geometries were tested in vitro. B 0 field distortion maps were measured via the frequency shift Δ f using multi-echo imaging. B1 distortions were quantified using the double angle method. The relative amplitudes B 1 rel were calculated to compare the intraluminal alteration of B1 . Measurements were repeated with the stents in three different orientations: parallel, diagonal and orthogonal to B 0 . Results: At 1.5 T, the braided stents induced a maximum frequency shift of Δ f x < 100 H z . Signal voids were limited to a distance of 2 mm to the stent walls at an echo time of 3 ms. No substantial difference in the B 0 field distortions was seen between laser-cut and braided venous stents. B 1 rel maps showed strongly varying distortion patterns in the braided stents with the mean intraluminal B 1 rel ranging from 63 ± 18 % in prototype 1 to 98 ± 38 % in prototype 2. Compared to laser-cut stents the braided stents showed a 5 to 9 times higher coefficient of variation of the intraluminal B 1 rel . Conclusion: Braided venous stent prototypes allow for MR imaging of the intraluminal area without substantial signal voids due to B 0 -induced artifacts. Whereas B 1 is attenuated homogeneously in laser-cut stents, the B 1 distortion in braided stents is more inhomogeneous and shows areas with enhanced amplitude. This could potentially be used in braided stent designs for intraluminal signal amplification.